Effects of Inorganic Fillers on the Thermal and Mechanical Properties of Poly(lactic acid) - Yang, Mingshu; Chow, Laurence C.; Wang, Tongxin; Liu, Xingxun; Mitchell, James W. (International Journal of Polymer Science, 2014)
Addition of filler to polylactic acid (PLA) may affect its crystallization behavior and mechanical properties. The effects of talc and hydroxyapatite (HA) on the thermal and mechanical properties of two types of PLA (one amorphous and one semicrystalline) have been investigated. The composites were prepared by melt blending followed by injection molding. The molecular weight, morphology, mechanical properties, and thermal properties have been characterized by gel permeation chromatography (GPC), scanning electron microscope (SEM), instron tensile tester, thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), and dynamic mechanical analysis (DMA). It was found that the melting blending led to homogeneous distribution of the inorganic filler within the PLA matrix but decreased the molecular weight of PLA. Regarding the filler, addition of talc increased the crystallinity of PLA, but HA decreased the crystallinity of PLA. The tensile strength of the composites depended on the crystallinity of PLA and the interfacial properties between PLA and the filler, but both talc and HA filler increased the toughness of PLA.